Resolving Disputes Regarding Trust Financing in Islamic Rural Banks, West Java - Ahmad Maulidizen (Journal of Islamic Law and Legal Studies, 2024)
One form of Islamic banking financing is mudarabah, which is a profit and loss sharing contract between an Islamic bank and a mudarib. This type of contract requires a mutually open attitude between both parties to the advantages and disadvantages of the project undertaken. Therefore, banks should implement a system of monitoring and assessment of project criteria well to avoid risks that may cause bank losses as sahib al-mal. This research uses a mixed method of research, with data collection methods as interviews, questionnaire, observation and document analysis. Which is then analyzed qualitatively by analysis from interviews and observations. For quantitative analysis, factor analysis, regression and Analysis of Variance (ANOVA) are conducted. The results of this research are the criteria of projects that need to be supervised by Islamic banking, which are Project Profiles, Payment Guarantee, Project Management, and Prospect project. If the assessment of project criteria is tightened and implemented correctly, mudarabah financing issues can be reduced and resolved.